2021
DOI: 10.3390/s21217165
|View full text |Cite
|
Sign up to set email alerts
|

A New Trajectory Tracking Algorithm for Autonomous Vehicles Based on Model Predictive Control

Abstract: Trajectory tracking is a key technology for precisely controlling autonomous vehicles. In this paper, we propose a trajectory-tracking method based on model predictive control. Instead of using the forward Euler integration method, the backward Euler integration method is used to establish the predictive model. To meet the real-time requirement, a constraint is imposed on the control law and the warm-start technique is employed. The MPC-based controller is proved to be stable. The simulation results demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…To meet the real-time requirement, a constraint is imposed on the control law, and the warm-start technique is employed. The authors of [7] concluded that the proposed the tracking performance of the proposed controller is much better than that of controllers using the forward Euler method.…”
Section: About the Editorsmentioning
confidence: 96%
See 3 more Smart Citations
“…To meet the real-time requirement, a constraint is imposed on the control law, and the warm-start technique is employed. The authors of [7] concluded that the proposed the tracking performance of the proposed controller is much better than that of controllers using the forward Euler method.…”
Section: About the Editorsmentioning
confidence: 96%
“…This Special Issue of Sensors aims at reporting on some of the recent research efforts on this increasingly important topic. The 12 accepted papers in this Issue cover vehicle position estimation [1], vehicle dynamic parameters estimation [2], cooperative collision warning systems [3], small object detection [4], impact identification of the driver's driving performance on executive control function [5], hybrid path planning for autonomous driving [6], trajectory tracking for autonomous driving [7], vehicle stability control [8], vehicle stability and ride comfort control [9], urban platooning protocol design for platoon [10], path planning algorithm for platooning [11], and self-driving architecture design for CAV platoon [12].…”
Section: About the Editorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the continuous state-space model of Equation ( 5) can be transformed into the discrete-time state-space model using the backward Euler technique [34]. Although the forward Euler method requires an extra computation at each iteration, the backward Euler method has great stability properties, and its local truncation error is much smaller than using the forward Euler method [35]. Therefore:…”
Section: Model Predictive Control Of the H8 Transformerless Invertermentioning
confidence: 99%